EXPERIMENTAL TEST OF COMPRESSIVE STRENGTH OF CONCRETE WITH SUBSTITUTION OF WASTE TYRE RUBBER POWDER 0%, 30%, 60% AS A SUBSTITUTE FOR FINE AGGREGATE - Guntur Nugroho (Acceleration: Multidisciplinary Research Journal, 2025)
The disposal of rubber tires is one of the impacts resulting from the development of activities in the transportation sector. The accumulation of tire waste occurs along with the increase in the number of vehicle owners in society. This study aims to test the compressive strength of concrete with a mixture of rubber powder waste to reduce environmental pollution. The method used is the experimental method in the laboratory with concrete cylinder test specimens measuring 150 mm in diameter and 300 mm in height. The proportion of the rubber powder waste mixture to the fine aggregate was 0%, 30%, and 60%, consisting of three cylindrical test specimens for each variation. The test results show compressive strength values of 26.8 MPa, 19.6 MPa, and 13.1 MPa at rubber powder mixture percentages of 0%, 30%, and 60%. From the data, it can be concluded that rubber powder can be used as a partial substitute for sand in concrete material. The use of rubber powder in concrete reduces the compressive strength of the concrete.